Association between Galectin-13 Expression and Eosinophilic Airway Inflammation in Chronic Obstructive Pulmonary Disease. (31st December 2023) - Yi, Lingling; Feng, Yuchen; Chen, Dian; Jin, Yanling; Zhang, Shuchen
Abstract: Chronic obstructive pulmonary disease (COPD) and asthma are chronic inflammatory diseases of the airways. Galectin-13 has recently been forwarded as a biomarker for airway eosinophilic inflammation in asthma. However, the association between galectin-13 and COPD remains unknown. To examine the changes in galectin-13 expression in acute exacerbations of COPD (AECOPD) and the stable phase of COPD and unveil the association between galectin-13 expression and eosinophilic inflammation in COPD, we measured plasma galectin-13 expression in different phases of COPD patients ( n  = 60, 44 AECOPD patients, and 16 stable COPD patients) and healthy controls ( n  = 15). Plasma levels of galectin-13 in 60 COPD patients were further analyzed and compared to systemic inflammation, airway eosinophilic inflammation, and lung function. The plasma galectin-13 level was markedly increased in subjects with AECOPD compared to stable COPD patients and healthy controls. Plasma galectin-13 levels in COPD subjects were positively correlated with serum CRP ( rs  = 0.46, p  = 0.0003), peripheral blood eosinophilia count ( rs  = 0.57, p <0.0001), and FeNO ( rs  = 0.46, p  = 0.0002). In addition, the level of galectin-13 was negatively correlated with FEV1 ( rs  = −0.43, p  = 0.0001), FEV1 pred (%) ( rs  = −0.544, p <0.0001), as well as FEV1 /FVC ( rs  = −0.46, p <0.0001). Multiple linear regression analysis suggested that plasma galectin-13 levels were affected by FEV1 pred (%), peripheral blood eosinophilia count, and FeNO. We concluded that galectin-13 levels were increased in COPD patients, and elevated galectin-13 expressions related to airway eosinophilic inflammation. Galectin-13 may facilitate the identification of COPD endotypes and may become a potential therapeutic target.